The Influence of Sharia Financial Performance Towards Islamic Social Reporting with Islamic Corporate Governance as a Moderate Variable - Fatima Az-zahra Wairooy (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2024)
This study examine to retest the influence of Sharia Financial Performance towards Islamic Social Reporting with Islamic Corporate Governance as a moderate variable (empirical study on Indonesia Islamic Commercial Bank from 2014-2021). The hypothesis examine by using MRA regression and panel data regression. The population in this research are all the Islamic Commercial Banks that listed on OJK from 2014-2021. The sampling methods that used in this research is purposive sampling and could manage to obtained 96 sample from 12 Islamic Commercial Banks. The results shows that: (1) Return On Assets, Capital Adequacy Ratio, and Debt to Equity Ratio did not influenced the Islamic Social Reporting; (2) Financing to Debt Ratio influenced the disclosure did Islamic Social Reporting; and (3) Board of Commissioner could influenced Return On Assets towards deepening of Islamic Social Reporting, Islamic Supervisory Board could be moderating Return On Assets, Financing to Debt Ratio and Capital Adequacy Ratio towards strengthening Islamic Social Reporting, While the age of the companies could moderating Return On Assets, and Financing to Debt Ratio towards Islamic Social Reporting.